2015
DOI: 10.1556/avet.2015.008
|View full text |Cite
|
Sign up to set email alerts
|

Fertilisation rate obtained with frozen-thawed boar semen supplemented with rosmarinic acid using a single insemination timed according to vulvar skin temperature changes

Abstract: Artificial insemination (AI) of sows with frozen-thawed semen usually results in lower pregnancy rates and litter sizes than the use of liquid preserved semen. The present study evaluated the effectiveness of vulvar skin temperature changes as a predictor of ovulation in sows and determined the fertility rates obtained after AI with frozen-thawed semen supplemented with rosmarinic acid (RA). Semen was collected from mature boars and cryopreserved in experimental extenders supplemented with or without 105 µM of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Deep intrauterine insemination with reduced number of sperm (1,000 x 10 6 ) 49 77.55 9.31 ± 0.41 Roca, Carvajal, Lucas, Vázquez, and Martínez (2003) Freezing medium supplemented with caffeine and CaCl 2 21 71.4 8.2 ± 0.9 Yamaguchi, Funahashi, and Murakami (2009) Freezing medium supplemented with cholesterol-loaded cyclodextrins 34 52.9 11.3 ± 0.9 Tomás, Blanch, Cebrián, and Mocé (2013) Addition of oxytocin to the thawed sperm suspension immediately before AI 48 88.8 8.4 ± 0.5 Okazaki et al (2014) Freezing medium supplemented with rosmarinic acid 10 55.3 9.7 ± 0.4 Luño et al (2015) Freezing medium supplemented with 6.0 mg/ ml of alpha-lipoic acid 20 75 10.1 ± 1.1 Shen, Jiang, Li, Hu, and Li (2016) pig breeds: Duroc, Large White and Landrace (Ma et al, 2013).…”
Section: No Of Young Per Litter Referencementioning
confidence: 99%
“…Deep intrauterine insemination with reduced number of sperm (1,000 x 10 6 ) 49 77.55 9.31 ± 0.41 Roca, Carvajal, Lucas, Vázquez, and Martínez (2003) Freezing medium supplemented with caffeine and CaCl 2 21 71.4 8.2 ± 0.9 Yamaguchi, Funahashi, and Murakami (2009) Freezing medium supplemented with cholesterol-loaded cyclodextrins 34 52.9 11.3 ± 0.9 Tomás, Blanch, Cebrián, and Mocé (2013) Addition of oxytocin to the thawed sperm suspension immediately before AI 48 88.8 8.4 ± 0.5 Okazaki et al (2014) Freezing medium supplemented with rosmarinic acid 10 55.3 9.7 ± 0.4 Luño et al (2015) Freezing medium supplemented with 6.0 mg/ ml of alpha-lipoic acid 20 75 10.1 ± 1.1 Shen, Jiang, Li, Hu, and Li (2016) pig breeds: Duroc, Large White and Landrace (Ma et al, 2013).…”
Section: No Of Young Per Litter Referencementioning
confidence: 99%
“…) have only minimal effects on in vivo fertility (Luño et al. ). Similarly, not all sperm additives, such as caffeine (Yamaguchi et al.…”
Section: Cryopreserved Sperm Additivesmentioning
confidence: 99%
“…Excellent fertility (>90% farrowing rate and 13.0 total born) was obtained with glutathione addition when using a total of three billion frozenthawed sperm in a double IUI. However, not all antioxidants have worked as well and might be attributed to the concentration and the freezing conditions (Buranaamnuay et al 2011a), or perhaps while improv-ing in vitro sperm motility and viability and IVF (Luño et al 2014) have only minimal effects on in vivo fertility (Luño et al 2015). Similarly, not all sperm additives, such as caffeine (Yamaguchi et al 2009) or prostaglandin (Knox and Yantis 2014) have worked well to improve fertility when used with AI.…”
Section: Cryopreserved Sperm Additivesmentioning
confidence: 99%
“…In a different approach, considering the effect of ambient temperature, simultaneously observing the temperature change of vulva and other body parts (gluteal area, udder, and ear base), or the temperature difference change between these body parts and vulvar skin temperature. The results showed that changes in vulvar skin temperature were the most correlated with estrus and that the mean temperature of vulvar skin of gilts and multiparous sows increased at the onset of estrus and decreased before ovulation [3,[23][24][25] . Moreover, the validity of vulvar skin average temperature variation as a predictor of sow ovulation was evaluated by inseminating sows once when the vulvar skin temperature of diestrous sows was 20% increased [1] or below 35°C [26] , where the threshold of 35°C resulted from Luño et al [18] The results showed comparable reproductive performance with the multiple insemination strategy of the conventional back-pressure test.…”
Section: Introductionmentioning
confidence: 99%